2013
DOI: 10.1097/cji.0b013e31829d8a1b
|View full text |Cite
|
Sign up to set email alerts
|

Treatment Efficacy and Immune Stimulation by AdCD40L Gene Therapy of Spontaneous Canine Malignant Melanoma

Abstract: Malignant melanoma is a serious disease in both humans and dogs, and the high metastatic potential results in poor prognosis for many patients. Its similarities with human melanoma make spontaneous canine melanoma an excellent model for comparative studies of novel therapies and tumor biology. We report a pilot study of local adenovector CD40L (AdCD40L) immunogene treatment in 19 cases of canine melanoma (14 oral, 4 cutaneous, and 1 conjunctival). Three patients were World Health Organization stage I, 2 were s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
56
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(58 citation statements)
references
References 40 publications
0
56
0
2
Order By: Relevance
“…Recently, it was demonstrated that local administration of agonistic CD40 antibodies into tumorbearing mice resulted in improved antitumor effect, and caused less adverse immune-related events than systemic treatment (4,14,15). The concept of intratumoral CD40 stimulation has also been validated using local injection of adenoviral vectors expressing CD40L, demonstrating antitumor effects in human and murine bladder cancer as well as in dog melanoma, with minimal side effects (16,17).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it was demonstrated that local administration of agonistic CD40 antibodies into tumorbearing mice resulted in improved antitumor effect, and caused less adverse immune-related events than systemic treatment (4,14,15). The concept of intratumoral CD40 stimulation has also been validated using local injection of adenoviral vectors expressing CD40L, demonstrating antitumor effects in human and murine bladder cancer as well as in dog melanoma, with minimal side effects (16,17).…”
Section: Introductionmentioning
confidence: 99%
“…When one such molecule CD40, a receptor found on the surface of B cells and APCs binds to CD40L expressed on T-cells it activates the CD40 bearing cells and thus enhances humoural as well as cell mediated immunity (Elgueta et al, 2009). Treatment of CMM with a replicate deficient adenovirus expressing CD40L administered intra-tumourally has been piloted (dVon Euler et al, 2008von Euler et al, 2008 and succeded by a larger clinical trial of CMM patients (Westberg et al, 2013). The use of viral agents as cancer immunotherapeutics is a rapidly growing field and results from on-going human and veterinary trials are eagerly awaited.…”
Section: Adaptive Iimmunitymentioning
confidence: 99%
“…Several comparative studies of novel immunotherapy protocols have been performed in dogs affected by MM, and promising results have been achieved [87][88][89][90][91]. These efforts led to the development of the first USDA-approved antitumor vaccine; ONCEPT (Merial), a xenogeneic DNA vaccine targeting tyrosinase which can extend survival in dogs with locally controlled stage II-III oral MM.…”
Section: Melanomamentioning
confidence: 99%